The 5 Pillars in Tourette Syndrome Deep Brain Stimulation Patient Selection: Present and Future. (6th April 2021) - Martino, Davide; Deeb, Wissam; Jimenez-Shahed, Joohi; Malaty, Irene; Pringsheim, Tamara M.; Fasano, Alfonso; Ganos, Christos; Wu, Winifred; Okun, Michael S.
Abstract : The selection of patients with Tourette syndrome (TS) for deep brain stimulation (DBS) surgery rests on 5 fundamental pillars. However, the operationalization of the multidisciplinary screening process to evaluate these pillars remains highly diverse, especially across sites. High tic severity and tic-related impact on quality of life (first 2 pillars) require confirmation from objective, validated measures, but malignant features of TS should per se suffice to fulfill this pillar. Failure of behavioral and pharmacologic therapies (third pillar) should be assessed taking into account refractoriness through objective and subjective measures supporting lack of efficacy of all interventions of proven efficacy, as well as true lack of tolerability, adherence, or access. Educational interventions and use of remote delivery formats (for behavioral therapies) play a role in preventing misjudgment of treatment failure. Stability of comorbid psychiatric disorders for 6 months (fourth pillar) is needed to confirm the predominant impact of tics on quality of life, to prevent pseudo-refractoriness, and to maximize the future DBS response. The 18-year age limit (fifth pillar) is currently under reappraisal, considering the potential impact of severe tics in adolescence and the predictive effect of tic severity in childhood on tic severity when transitioning into adulthood. Future advances should aim at a consensus-based definition of failure of specific, noninvasive treatment strategies for tics and of the minimum clinical observation period before considering DBS treatment, the stability of behavioral comorbidities, and the use of a prospective international registry data to identify predictors of positive response to DBS, especially in younger patients.